Intrincada construcción de identidad profesional y relaciones de poder: percepciones en docentes universitarios de Educación Física (Intricate construction of professional identity and power relations: perceptions in university Physical Education teachers) - Maquera-Maquera, Yanet Amanda; Bermejo-Paredes, Saúl; Olivera Condori, Erika; Cahuana Tapia, Rogelio Domingo; Pino Vanegas , Yony Martín; Yupanqui Pino, Efrain Humberto; Chuquicallata Paricahua, Silo Nahun; Vilca Apaza, Henry Mark (Retos, 2024)
Physical Education (PE) teachers, faced with the demands of a complex and changing society, warn that they are being placed before the educational system, as one of the main responsible for the crisis that university education is going through, events that disrupt the sense of professional identity forged during years of initial and in-service training. Aim. Understand the construction of representations of professional identity in a context of intersubjective positions of power based on interactive/reflective discourses among university PE teachers. Method. Qualitative, inductive, open coding, dynamic and interactive with support in Atlas.ti 8, for data analysis. Results. It is not possible to identify constructs-perceptions of professional identity, detached from a network, a field of very subtle arrangements and dissents that define positions, alliances, oppositions and intersubjective power relations among university PE teachers; Teachers go through tortuous experiences that prevent them from building their own identity; what exists is an attributed and pre-established identity; They associate their identity with “should be”, regulated-supervised by institutional-normative management and with ways of responding to the expectations and interests of others. Conclusion. In the current university management model, the teacher, in addition to assuming an attributed identity, linked to structural positions of dominance-subordination, experiences certain external pressures to abdicate his vocation and professional training in favor of the idea of ​​becoming a scientific and bureaucratic being. out of obligation. Institutional programs are needed to build university identity processes. Keywords: professional identity, university identity, university teaching, professional training, power relations, physical education teacher.